Knowledge and Practice of Medical Ethics, Negligence, and Patient Safety among Healthcare Professionals in a Tertiary Care Center in Central Nepal - Shrestha, Kaschev; Upadhyay, Hari Prasad; Upreti, Arish; Yadav , Yoveen Kumar; Palikhe, Devendra Man; Shrestha, Natasha (Journal of College of Medical Sciences-Nepal, 2025)
Background: Medical ethics, patient safety, and awareness of medical negligence are fundamental components of quality healthcare. Healthcare professionals’ knowledge and practices in these areas are critical to ensuring patient well-being and ethical clinical conduct. Previous studies in Nepal and South Asia have highlighted gaps in ethical knowledge and inconsistent practices among doctors, nurses, and medical students. The objective of this study is to assess the knowledge and practices related to medical ethics, medical negligence, and patient safety among healthcare professionals in a tertiary care center in Central Nepal. Methods: A cross-sectional study was conducted among 207 healthcare professionals. Data on sociodemographic characteristics and knowledge levels were collected using a structured questionnaire. Knowledge was categorized as low (<50%), average (50-70%), and excellent (>70%). Descriptive statistics and chi-square tests were applied to explore associations between knowledge and sociodemographic variables. Results: The majority of participants (72.9%) demonstrated excellent knowledge, 19.3% had average knowledge, and 7.7% showed low knowledge. None of the variables were found to be statistically significant (p-value>0.05). Conclusion: The study shows that healthcare professionals in Central Nepal have strong knowledge of medical ethics, patient safety, and medical negligence. Most participants understood key ethical principles and demonstrated confidence in managing ethical dilemmas. Despite gaps in formal training and access to ethics committees, adherence to safety protocols was high across all professional groups. These findings emphasize the need for structured ethics education and regular training to further strengthen ethical practices in clinical settings.